Acylcarnitine profile in Alaskan sled dogs during submaximal multiday exercise points out metabolic flexibility and liver role in energy metabolism. - Irene Tosi (Public Library of Science (PLoS), 2021)
Alaskan sled dogs develop a particular metabolic strategy during multiday submaximal exercise, allowing them to switch from intra-muscular to extra-muscular energy substrates thus postponing fatigue. Specifically, a progressively increasing stimulus for hepatic glycogenolysis and gluconeogenesis provides glucose for both fueling exercise and replenishing the depleted muscle glycogen. Moreover, recent studies have shown that with continuation of exercise sled dogs increase their insulin-sensitivity and their capacity to transport and oxidize glucose and carbohydrates rather than oxidizing fatty acids. Carnitine and acylcarnitines (AC) play an essential role as metabolic regulators in both fat and glucose metabolism; they serve as biomarkers in different species in both physiologic and pathologic conditions. We assessed the effect of multiday exercise in conditioned sled dogs on plasma short (SC), medium (MC) and long (LC) chain AC by tandem mass spectrometry (MS/MS). Our results show chain-specific modification of AC profiles during the exercise challenge: LCACs maintained a steady increase throughout exercise, some SCACs increased during the last phase of exercise and acetylcarnitine (C2) initially increased before decreasing during the later phase of exercise. We speculated that SCACs kinetics could reflect an increased protein catabolism and C2 pattern could reflect its hepatic uptake for energy-generating purposes to sustain gluconeogenesis. LCACs may be exported by muscle to avoid their accumulation to preserve glucose oxidation and insulin-sensitivity or they could be distributed by liver as energy substrates. These findings, although representing a "snapshot" of blood as a crossing point between different organs, shed further light on sled dogs metabolism that is liver-centric and more carbohydrate-dependent than fat-dependent and during prolonged submaximal exercise.